A 40-Year-Old Male Patient With Encephalopathy Hypertension And Emergency Hypertension With Sinus Tachycardia And Acute Kidney Injury. A Case Report. - Asrina Rery Kahowi; Veny Vicy Vidy Mandang; Vidithya Lindawati (Health & Medical Sciences, 2024)
We present the case of A male 40 years old with Encephalopathy Hypertension and Emergency Hypertension with Sinus Tachycardia and Acute Kidney Injury. the patient was diagnosed with hypertensive encephalopathy based on clinical criteria upon admission to the hospital, compared to the patient's condition when allowed to go home. Electrocardiography, chest x-ray, and laboratory examinations such as kidney function tests, liver function tests, and complete blood count were performed to identify other complications of hypertensive emergency. This patient was taken to the ER due to decreased consciousness after a seizure occurring shortly before being admitted. After a comprehensive physical examination, a blood pressure of 260/110 was recorded, and the patient exhibited decreased consciousness: GCS eye 4, verbal 3, motor 5. The patient was given intravenous anti-hypertensi to reduce blood pressure according to the recommended MAP, which is a 20-25% decrease in one hour. Subsequently, the patient's blood pressure normalized, and slowly, the patient's consciousness returned to normal. The patient was stable and, on the third day of treatment, was discharged with normal blood pressure and no neurological deficits.